Tomotherapy – a different way of dose delivery in radiotherapy - Piotrowski, Tomasz; Skórska, Małgorzata; Jodda, Agata; Ryczkowski, Adam; Kaźmierska, Joanna; Adamska, Krystyna; Karczewska-Dzionk, Aldona; Żmijewska-Tomczak, Małgorzata; Włodarczyk, Hanna (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Helical tomotherapy is one of the methods of radiotherapy. This method enables treatment implementation for a wide spectrum of clinical cases. The vast array of therapeutic uses of helical tomotherapy results directly from the method of dose delivery, which is significantly different from the classic method developed for conventional linear accelerators. The paper discusses the method of dose delivery by a tomotherapy machine. Moreover, an analysis and presentation of treatment plans was performed in order to show the therapeutic possibilities of the applied technology. Dose distributions were obtained for anaplastic medulloblastoma, multifocal metastases to brain, vulva cancer, tongue cancer, metastases to bones, and advanced skin cancer. Tomotherapy treatment plans were compared with conventional linear accelerator plans. Results : Following the comparative analysis of tomotherapy and conventional linear accelerator plans, in each case we obtained the increase in dose distribution conformity manifested in greater homogeneity of doses in the radiation target area for anaplastic medulloblastoma, multifocal metastases to brain, vulva cancer, metastases to bones, and advanced skin cancer, and the reduction of doses in organs at risk (OAR) for anaplastic medulloblastoma, vulva cancer, tongue cancer, and advanced skin cancer. The time of treatment delivery in the case of a tomotherapy machine is comparable to the implementation of the plan prepared in intensity-modulated radiotherapy (IMRT) technique for a conventional linear accelerator. In the case of tomotherapy the application of a fractional dose was carried out in each case during one working period of the machine. For a conventional linear accelerator the total value of the fractional dose in the case of anaplastic medulloblastoma and metastases to bones was delivered using several treatment plans, for which a change of set-up was necessary during a fraction. Conclusion : The obtained results confirm that tomotherapy offers the possibility to obtain precise treatment plans together with the simplification of the therapeutic system.